Adhesive for electronic material and liquid crystal display element
By developing a specific adhesive for electronic materials, including curable resin and surface-treated inorganic filler, the problem of adhesive remaining on the inner wall of the syringe is solved, and excellent descriptiveness and liquid crystal insertion effect is achieved.
Patent Information
- Application Number
- CN202411167630.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-16
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-25
AI Technical Summary
The adhesive for electronic materials remains on the inner wall of the syringe, causing the adhesive to detach again and introduce air bubbles, affecting the quality of the drawing and sealing performance.
Developed an adhesive for electronic materials containing a curable resin and an inorganic filler, with a viscosity of 1.5 million mPa·s or less, a thixotropy index of 3.0 or more and 5.0 or less, and a content of inorganic filler relative to 100 mass of the curable resin Parts are 30 parts by mass or more.
The effect of not remaining adhesive on the inner wall of the syringe is achieved, while maintaining excellent descriptiveness and preventing liquid crystal insertion.
Smart Images

Figure BDA0005008299950000231 
Figure BDA0005008299950000241
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive for electronic materials and a liquid crystal display element formed by using the adhesive for electronic materials. Background Art
[0002] In recent years, liquid crystal display elements and organic EL display elements have been widely used as display elements with characteristics such as thinness, lightness, and low power consumption. In such display elements and other electronic devices, adhesives for electronic materials are usually used for bonding various components, sealing liquid crystals or light-emitting layers, etc.
[0003] For example, in recent years, as a manufacturing method for liquid crystal display elements such as liquid crystal display units, from the perspective of shortening the production cycle time and optimizing the amount of liquid crystal used, a liquid crystal dripping method called a dripping process, which uses an adhesive for electronic materials as a sealant as disclosed in Patent Documents 1 and 2, has been used. In the dripping process, first, a frame-shaped sealing pattern is formed on one of two substrates with electrodes by dispensing. Next, tiny drops of liquid crystal are dripped into the sealing frame of the substrate in an uncured state of the sealant, and another substrate is overlapped under vacuum to cure the sealant to produce a liquid crystal display element. At present, this dripping process has become the mainstream of the manufacturing method of liquid crystal display elements.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-133794
[0007] Patent document 2: International Publication No. 02 / 092718 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The adhesive for electronic materials is usually filled in the syringe for distribution and continued to be used after degassing, but if the adhesive for electronic materials remains in the wall of the syringe, the residual adhesive for electronic materials falls into the adhesive for electronic materials in the syringe again due to the vibration of the device, so that the adhesive for electronic materials sometimes becomes an adhesive containing bubbles. The adhesive for electronic materials containing bubbles is prone to poor drawing such as broken lines, so it is required that no adhesive for electronic materials remain on the wall in the syringe. As a method for making the adhesive for electronic materials not remain in the wall in the syringe, it is considered to reduce the viscosity of the adhesive for electronic materials. However, if the viscosity of the adhesive for electronic materials is reduced, there is a problem that the fine line drawing property deteriorates or the phenomenon that liquid crystal insertion sealant is easily generated when the adhesive for electronic materials is used as a sealant for liquid crystal display elements.
[0010] An object of the present invention is to provide an adhesive for electronic materials having excellent drawing properties and a property of preventing wall residue in a syringe. Another object of the present invention is to provide a liquid crystal display element formed by using the adhesive for electronic materials.
[0011] Means for solving problems
[0012] The present invention 1 relates to an adhesive for electronic materials, which contains a curable resin and an inorganic filler, and has a viscosity of 1.5 million mPa·s or less measured using an E-type viscometer under the conditions of 25° C. and 0.01 rpm, and a thixotropic index of the adhesive for electronic materials of 3.0 or more and 5.0 or less, wherein the thixotropic index is a value obtained by dividing the viscosity measured using an E-type viscometer under the conditions of 25° C. and 0.01 rpm by the viscosity measured under the conditions of 25° C. and 1 rpm.
[0013] Invention 2 is the adhesive for electronic materials according to invention 1, wherein the content of the inorganic filler is 30 parts by mass or more based on 100 parts by mass of the curable resin.
[0014] The third aspect of the present invention relates to the adhesive for electronic materials of the first or second aspect of the present invention, wherein the inorganic filler comprises an inorganic filler surface-treated with a surface treatment agent, and the polar component δp of the Hansen solubility parameter of the surface treatment agent is 3.5 MPa. 0.5 Above and 6.0MPa 0.5 the following.
[0015] The present invention 4 is directed to the adhesive for electronic materials according to the present invention 1, 2 or 3, wherein in the particle size distribution of the inorganic filler, a particle size D50 at which the cumulative mass from the minimum particle size side becomes 50% is 300 nm or more.
[0016] Invention 5 relates to an adhesive for electronic materials according to invention 1, 2, 3 or 4, wherein in the particle size distribution of the inorganic filler, the particle size D50 at which the cumulative mass from the minimum particle size side becomes 50% is less than 2 μm, and the particle size D100 at which the cumulative mass from the minimum particle size side becomes 100% is less than 6 μm.
[0017] Invention 6 relates to an adhesive for electronic materials according to invention 1, 2, 3, 4 or 5, wherein in the particle size distribution, it does not contain an organic filler having a particle size D50 of 50 nm or more and 500 nm or less, at which the cumulative mass from the minimum particle size side becomes 50%, or the content of the organic filler having a D50 of 50 nm or more and 500 nm or less is less than 10 parts by mass relative to 100 parts by mass of the above-mentioned curable resin.
[0018] The present invention 7 relates to a liquid crystal display element comprising a cured product of the adhesive for electronic materials according to the present invention 1, 2, 3, 4, 5 or 6.
[0019] Hereinafter, the present invention will be described in detail.
[0020] The present inventors have studied how to adjust the viscosity measured at a low speed using an E-type viscometer to a specific value or more and the thixotropic index to a specific range in an adhesive for electronic materials containing a curable resin and an inorganic filler. As a result, they found that an adhesive for electronic materials having excellent drawing properties and wall residue prevention properties in a syringe can be obtained, thereby completing the present invention.
[0021] The upper limit of the viscosity of the adhesive for electronic materials of the present invention measured using an E-type viscometer at 25°C and 0.01 rpm is 1.5 million mPa·s. By making the above viscosity 1.5 million mPa·s or less, the wall residue prevention property in the syringe of the adhesive for electronic materials of the present invention is excellent. The preferred upper limit of the above viscosity is 1.3 million mPa·s, and the more preferred upper limit is 1.1 million mPa·s.
[0022] In addition, from the viewpoint of drawing properties and the like, the lower limit of the viscosity is preferably 600,000 mPa·s, and the more preferred lower limit is 800,000 mPa·s.
[0023] As the E-type viscometer, for example, DV-III (manufactured by Brookfield Co., Ltd.) or the like can be used.
[0024] The thixotropic index (hereinafter also referred to as "Ti value") of the adhesive for electronic materials of the present invention has a lower limit of 3.0 and an upper limit of 5.0, and the thixotropic index is a value obtained by dividing the viscosity measured at 25 ° C and 0.01 rpm using an E-type viscometer by the viscosity measured at 25 ° C and 1 rpm. By making the above-mentioned Ti value into this range, the adhesive for electronic materials of the present invention has excellent depictability. In addition, if the above-mentioned Ti value is in this range, when the adhesive for electronic materials of the present invention is used as a sealant for liquid crystal display elements, the effect of preventing the insertion of liquid crystals is also excellent. The preferred lower limit of the above-mentioned Ti value is 3.2, the preferred upper limit is 4.8, the more preferred lower limit is 3.4, and the more preferred upper limit is 4.6.
[0025] Examples of methods for adjusting the viscosity and the Ti value to fall within the above ranges include a method of adjusting the type and content of each component such as a curable resin and an inorganic filler, which will be described later.
[0026] The adhesive for electronic materials of the present invention contains an inorganic filler.
[0027] The inorganic filler has functions such as adjusting the viscosity of the adhesive for electronic materials, improving the adhesiveness, improving the linear expansion coefficient, and improving the moisture permeation resistance of the cured product.
[0028] Examples of the inorganic filler include silicon dioxide, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, calcium silicate, etc. Among them, silicon dioxide is preferred.
[0029] The inorganic filler preferably includes an inorganic filler surface-treated with a surface treatment agent. By using the inorganic filler surface-treated with the surface treatment agent, it is easier to adjust the viscosity and the Ti value of the obtained electronic material adhesive to the above range. In addition, by using the inorganic filler surface-treated with the surface treatment agent, the moisture permeability of the cured product of the obtained electronic material adhesive can also be improved.
[0030] As the group introduced into the surface of the inorganic filler by the surface treatment, for example, there can be mentioned: alkyl groups having 1 to 20 carbon atoms such as methyl, ethyl, propyl, butyl, hexyl, cyclohexyl, octyl, 2-ethylhexyl, lauryl, and stearyl, epoxy groups such as glycidyl and 3,4-epoxycyclohexyl, primary amino groups, secondary amino groups, tertiary amino groups, alkoxy groups, vinyl groups, (meth)acryloyl groups, thioether groups, mercapto groups, isocyanate groups, urea groups, pyridyl groups, styryl groups, ether bonds, ester bonds, thiol groups, etc. Among them, epoxy groups and (meth)acryloyl groups are preferred.
[0031] In addition, in this specification, the said "(meth)acryloyl group" means an acryloyl group or a methacryloyl group.
[0032] The preferred lower limit of the polar component δp of the Hansen solubility parameter of the surface treatment agent is 3.5 MPa. 0.5 The preferred upper limit is 6.0 MPa 0.5 By setting the δp of the surface treatment agent to be within the above range, it is easier to adjust the viscosity and the Ti value of the adhesive for electronic materials to be obtained to be within the above range.
[0033] It should be noted that the polar component δp of the Hansen solubility parameter can be derived by calculation based on the structural formula using HSP software. As the HSP software, Hansen Solubility Parameter in Practice (HSPiP) can be used.
[0034] Specific examples of the surface treatment agent include: silane coupling agents having an alkyl group such as methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, methyltrichlorosilane, butyltrichlorosilane, and trifluoropropyltrimethoxysilane; silane coupling agents having a phenyl group such as phenyltrimethoxysilane and phenyltriethoxysilane; 3- Silane coupling agents with epoxy groups, such as glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, and 2-(3,4-epoxycyclohexyl) ethyl trimethoxysilane; N-phenyl-3-aminopropyl trimethoxysilane, N-(2-aminoethyl) 3-aminopropyl methyl dimethoxysilane, N-(2-aminoethyl) 3-aminopropyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane Silane coupling agents having amino groups such as silane; vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri (2-methoxyethoxy) silane, vinyl methyl dimethoxy silane, vinyl methyl diethoxy silane, vinyl trichlorosilane, allyl trichlorosilane, allyl trimethoxysilane, allyl triethoxysilane, p-phenylene trimethoxysilane and other silane coupling agents having vinyl groups; 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl triethoxysilane, Silane coupling agents having a (meth)acryloyl group, such as 3-acryloxypropyltrimethoxysilane; mercapto and sulfur silane coupling agents, such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, and 3-octanoylthio-1-propyltriethoxysilane; urea silane coupling agents, such as 3-ureidopropyltriethoxysilane; isocyanate silane coupling agents, such as 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane, etc.
[0035] As a method for surface treating an inorganic filler (substrate particles) before surface treatment using the above-mentioned surface treatment agent, for example, there can be mentioned: a method of spraying a mixed solution of water and the above-mentioned surface treatment agent onto the above-mentioned substrate particles in a flowing state; a method of adding the above-mentioned substrate particles to an organic solvent such as alcohol or toluene, further adding the above-mentioned surface treatment agent and water, and then evaporating and drying the water and the organic solvent using an evaporator, etc.
[0036] The preferred lower limit of the particle size D50 of the inorganic filler at which the cumulative mass from the smallest particle size side in the particle size distribution is 50% is 300 nm. When the D50 is 300 nm or more, a sealant with better moisture permeation resistance is obtained. The more preferred lower limit of the D50 is 350 nm.
[0037] In addition, with respect to the inorganic filler, it is preferred that the particle size D50 at which the cumulative mass from the minimum particle size side is 50% in the particle size distribution is 2 μm or less, and the particle size D100 at which the cumulative mass from the minimum particle size side is 100% is 6 μm or less. By setting the D50 to 2 μm or less and the D100 to 6 μm or less, a sealant having better drawing properties is obtained. The D50 is more preferably 1 μm or less, and the D100 is more preferably 5 μm or less.
[0038] The particle size distribution can be measured using a particle size distribution measuring device. Examples of the particle size distribution measuring device include NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS Co., Ltd.).
[0039] The preferred lower limit of the content of the inorganic filler is 30 parts by mass relative to 100 parts by mass of the curable resin described later. By making the content of the inorganic filler 30 parts by mass or more, it is easier to adjust the viscosity and the Ti value of the obtained adhesive for electronic materials to the above range. In addition, by making the content of the inorganic filler 30 parts by mass or more, the light shielding curing property of the obtained adhesive for electronic materials also becomes excellent.
[0040] In addition, from the viewpoint of drawing properties and the like, the upper limit of the content of the inorganic filler is 85 parts by mass, and a more preferred upper limit is 50 parts by mass.
[0041] The adhesive for electronic materials of the present invention preferably does not contain an organic filler having a D50 of 50 nm or more and 500 nm or less, or the content of the organic filler having a D50 of 50 nm or more and 500 nm or less is 10 parts by mass or less relative to 100 parts by mass of the curable resin described later. The more preferred upper limit of the content of the organic filler having a D50 of 50 nm or more and 500 nm or less is 8 parts by mass, and the adhesive for electronic materials of the present invention most preferably does not contain an organic filler having a D50 of 50 nm or more and 500 nm or less.
[0042] The adhesive for electronic materials of the present invention contains a curable resin.
[0043] The curable resin preferably comprises at least one selected from epoxy compounds and (meth) acrylic compounds. By using the epoxy compounds and (meth) acrylic compounds in combination with a polymerization initiator and a thermosetting agent described later, the resulting adhesive for electronic materials can have excellent photocurability and thermosetting properties.
[0044] In addition, in this specification, the said "(meth)acrylic system" means an acrylic system or a methacrylic system.
[0045] Examples of the epoxy compound include bisphenol A epoxy compounds, bisphenol F epoxy compounds, bisphenol E epoxy compounds, bisphenol S epoxy compounds, 2,2'-diallylbisphenol A epoxy compounds, hydrogenated bisphenol epoxy compounds, propylene oxide-added bisphenol A epoxy compounds, resorcinol epoxy compounds, biphenyl epoxy compounds, sulfide epoxy compounds, diphenyl ether epoxy compounds, dicyclopentadiene epoxy compounds, and the like. Type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, o-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthol novolac type epoxy compounds (Japanese: ナフタレンフェノールノボラック type epoxide compounds), glycidylamine type epoxy compounds, alkyl polyol type epoxy compounds, rubber modified epoxy compounds, glycidyl ester compounds, etc.
[0046] As what is marketed among the said bisphenol A type epoxy compounds, jER828EL, jER1004 (all are manufactured by Mitsubishi Chemical Corporation), EPICLONEXA-850CRP (manufactured by DIC Corporation), etc. are mentioned, for example.
[0047] As what is marketed among the said bisphenol F type epoxy compounds, jER806, jER4004 (all are manufactured by Mitsubishi Chemical Corporation), EPICLON EXA-830CRP (manufactured by DIC Corporation), etc. are mentioned, for example.
[0048] As what is marketed among the said bisphenol E type epoxy compounds, EPOMIK R710 (made by Mitsui Chemicals, Inc.) etc. are mentioned, for example.
[0049] As what is marketed among the said bisphenol S type epoxy compounds, EPICLON EXA-1514 (made by DIC Corporation) etc. are mentioned, for example.
[0050] As what is marketed among the said 2,2'- diallylbisphenol A type epoxy compounds, RE-810NM (made by Nippon Kayaku Co., Ltd.) etc. are mentioned, for example.
[0051] As what is marketed among the said hydrogenated bisphenol type epoxy compounds, EPICLON EXA-7015 (made by DIC Corporation) etc. are mentioned, for example.
[0052] As what is marketed among the said propylene oxide addition bisphenol A type epoxy compound, EP-4000S (made by ADEKA Corporation) etc. are mentioned, for example.
[0053] As what is marketed among the said resorcinol type epoxy compounds, EX-201 (made by Nagase ChemteX Co., Ltd.) etc. are mentioned, for example.
[0054] As what is marketed among the said biphenyl type epoxy compounds, jERYX-4000H (made by Mitsubishi Chemical Corporation) etc. are mentioned, for example.
[0055] As what is commercially available among the said thioether type epoxy compounds, YSLV-50TE (made by NIPPON STEEL Chemical & Material Co., Ltd.) etc. are mentioned, for example.
[0056] As what is marketed among the said diphenyl ether type epoxy compounds, YSLV-80DE (made by NIPPONSTEEL Chemical & Material Co., Ltd.) etc. are mentioned, for example.
[0057] As what is marketed among the said dicyclopentadiene type epoxy compounds, EP-4088S (made by ADEKA Corporation) etc. are mentioned, for example.
[0058] Examples of commercially available products of the naphthalene-type epoxy compounds include EPICLON HP-4032 and EPICLONEX A-4700 (both manufactured by DIC Corporation).
[0059] As what is marketed among the said phenol novolac-type epoxy compounds, EPICLON N-770 (made by DIC Corporation) etc. are mentioned, for example.
[0060] As what is marketed among the said o-cresol novolac-type epoxy compounds, EPICLON N-670-EXP-S (made by DIC Corporation) etc. are mentioned, for example.
[0061] As what is marketed among the said dicyclopentadiene novolak-type epoxy compounds, EPICLON HP-7200 (made by DIC Corporation) etc. are mentioned, for example.
[0062] As what is marketed among the said biphenyl novolak-type epoxy compounds, NC-3000P (made by Nippon Kayaku Co., Ltd.) etc. are mentioned, for example.
[0063] As a commercial item among the said naphthol novolac-type epoxy compounds, ESN-165S (made by NIPPONSTEEL Chemical & Material Co., Ltd.) etc. are mentioned, for example.
[0064] Examples of commercially available products of the glycidylamine epoxy compounds include jER630 (manufactured by Mitsubishi Chemical Corporation), EPICLON 430 (manufactured by DIC Corporation), and TETRAD-X (manufactured by Mitsubishi Gas Chemical Corporation).
[0065] Examples of commercially available products of the alkyl polyol epoxy compounds include ZX-1542 (manufactured by Nippondeel Chemical & Material Co., Ltd.), Epiclon 726 (manufactured by DIC Corporation), EPOLIGHT 80MFA (manufactured by Kyoeisha Chemical Co., Ltd.), and Denacol EX-611 (manufactured by Nagase ChemteX Corporation).
[0066] Examples of commercially available products of the rubber-modified epoxy compound include YR-450 and YR-207 (both manufactured by NIPPON STEEL Chemical & Material Co., Ltd.) and Epolead PB (manufactured by Daicel Corporation).
[0067] As what is commercially available among the said glycidyl ester compound, Denacol EX-147 (made by Nagase ChemteX Co., Ltd.) etc. are mentioned, for example.
[0068] As other commercially available products of the above-mentioned epoxy compounds, for example, YDC-1312, YSLV-80XY, YSLV-90CR (all manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), XAC4151 (manufactured by Asahi Kasei Corporation), jER1031, jER1032 (all manufactured by Mitsubishi Chemical Corporation), EXA-7120 (manufactured by DIC Corporation), TEPIC (manufactured by Nissan Chemical Co., Ltd.), etc. can be mentioned.
[0069] As the epoxy compound, a partially (meth)acrylic acid-modified epoxy compound can also be suitably used.
[0070] It should be noted that in the present specification, the partially (meth)acrylic acid-modified epoxy compound refers to a compound having one or more epoxy groups and one or more (meth)acryloyl groups in one molecule, which can be obtained by reacting a part of the epoxy groups of an epoxy compound having two or more epoxy groups with (meth)acrylic acid.
[0071] As what is marketed among the said partial (meth)acrylic acid-modified epoxy compounds, UVACURE1561, KRM8287 (all are manufactured by DAICEL-ALLNEX CORPORATION) etc. are mentioned, for example.
[0072] As the above-mentioned (meth) acrylic acid compounds, for example, (meth) acrylic acid ester compounds, epoxy (meth) acrylates, urethane (meth) acrylates, etc. can be cited. Among them, epoxy (meth) acrylates are preferred. In addition, from the viewpoint of reactivity, the above-mentioned (meth) acrylic acid compounds preferably have two or more (meth) acryloyl groups in one molecule.
[0073] In addition, in this specification, the said "(meth)acrylate" means an acrylate or a methacrylate, and the said "epoxy (meth)acrylate" means the compound obtained by making all epoxy groups in an epoxy compound react with (meth)acrylic acid.
[0074] Examples of the monofunctional compound among the (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, and 2-ethoxyethyl (meth)acrylate. , 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, imide (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, glycidyl (meth)acrylate, and the like.
[0075] Examples of the bifunctional (meth)acrylate compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate. Ester, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide added bisphenol A di(meth)acrylate, propylene oxide added bisphenol A di(meth)acrylate, ethylene oxide added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, etc.
[0076] In addition, examples of the trifunctional or higher-functional compounds among the above-mentioned (meth)acrylate compounds include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerol tri(meth)acrylate, propylene oxide-added glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0077] As said epoxy (meth)acrylate, the epoxy (meth)acrylate etc. which are obtained by making an epoxy compound and (meth)acrylic acid react in the presence of a basic catalyst by a conventional method are mentioned, for example.
[0078] As the epoxy compound used as a raw material for synthesizing the epoxy (meth)acrylate, the same epoxy compound as that described above as the curable resin contained in the adhesive for electronic materials of the present invention can be used.
[0079] Examples of commercially available products of the epoxy (meth)acrylate include epoxy (meth)acrylate manufactured by Daicel-Allnex, epoxy (meth)acrylate manufactured by Shin-Nakamura Chemical Industry Co., Ltd., epoxy (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd., and epoxy (meth)acrylate manufactured by Nagase ChemteX.
[0080] Examples of the epoxy (meth)acrylate manufactured by DAICEL-ALLNEX include EBECRYL 860, EBECRYL 3200, EBECRYL 3201, EBECRYL 3412, EBECRYL 3600, EBECRYL 3700, EBECRYL 3701, EBECRYL 3702, EBECRYL 3703, EBECRYL 3708, EBECRYL 3800, EBECRYL 6040, EBECRYL KRM7985, and EBECRYL RDX63182.
[0081] As said epoxy (meth)acrylate manufactured by Shin-Nakamura Chemical Industry Co., Ltd., EA-1010, EA-1020, EA-5323, EA-5520, EA-CHD, EMA-1020 etc. are mentioned, for example.
[0082] Examples of the epoxy (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd. include Epoxy Ester M-600A, Epoxy Ester 40EM, Epoxy Ester 70PA, Epoxy Ester 200PA, Epoxy Ester 80MFA, Epoxy Ester 3002M, Epoxy Ester 3002A, Epoxy Ester 1600A, Epoxy Ester 3000M, Epoxy Ester 3000A, Epoxy Ester 200EA, and Epoxy Ester 400EA.
[0083] As said Nagase ChemteX epoxy (meth)acrylate, Denacol Acrylate DA-141, Denacol Acrylate DA-314, Denacol Acrylate DA-911 etc. are mentioned, for example.
[0084] The urethane (meth)acrylate can be obtained, for example, by reacting a (meth)acrylic acid derivative having a hydroxyl group with an isocyanate compound in the presence of a catalytic amount of a tin-based compound.
[0085] Examples of the isocyanate compound used as a raw material for the urethane (meth)acrylate include isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4′-diisocyanate (MDI), hydrogenated MDI, polymerized MDI, 1,5-naphthalene diisocyanate, Norbornane diisocyanate, dimethylbiphenyl diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphorothioate (Japanese: Tris(イソシアネートフェニル)チオフォスフェート), tetramethylxylylene diisocyanate, 1,6,11-undecane triisocyanate, etc.
[0086] Moreover, as the isocyanate compound used as the raw material of the above-mentioned urethane (meth)acrylate, a chain-extended isocyanate compound obtained by the reaction of a polyol with an excess of an isocyanate compound may be used.
[0087] Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0088] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of diols, mono(meth)acrylates or di(meth)acrylates of triols, and epoxy(meth)acrylates.
[0089] As said hydroxyalkyl mono(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate etc. are mentioned, for example.
[0090] Examples of the diol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol.
[0091] Examples of the triol include trimethylolethane, trimethylolpropane, and glycerin.
[0092] As said epoxy (meth)acrylate, bisphenol A type epoxy (meth)acrylate etc. are mentioned, for example.
[0093] Examples of commercially available products of the urethane (meth)acrylates include urethane (meth)acrylates manufactured by Toagosei Co., Ltd., urethane (meth)acrylates manufactured by Daicel-Allnex Co., Ltd., urethane (meth)acrylates manufactured by Negami Industries Co., Ltd., urethane (meth)acrylates manufactured by Shin-Nakamura Chemical Co., Ltd., and urethane (meth)acrylates manufactured by Kyoeisha Chemical Co., Ltd.
[0094] As the urethane (meth)acrylate manufactured by Toagosei Co., Ltd., for example, M-1100, M-1200, M-1210, and M-1600 can be mentioned.
[0095] Examples of the urethane (meth)acrylate manufactured by DAICEL-ALLNEX include EBECRYL 210, EBECRYL 220, EBECRYL 230, EBECRYL 270, EBECRYL 1290, EBECRYL 2220, EBECRYL 4827, EBECRYL 4842, EBECRYL 4858, EBECRYL 5129, EBECRYL 6700, EBECRYL 8402, EBECRYL 8803, EBECRYL 8804, EBECRYL 8807, and EBECRYL 9260.
[0096] Examples of the urethane (meth)acrylate manufactured by Negami Industries include Artresin UN-330, Artresin SH-500B, Artresin UN-1200TPK, Artresin UN-1255, Artresin UN-3320HB, Artresin UN-7100, Artresin UN-9000A, and Artresin UN-9000H.
[0097] Examples of the urethane (meth) acrylate manufactured by Shin-Nakamura Chemical Industry Co., Ltd. include U-2HA, U-2PHA, U-3HA, U-4HA, U-6H, U-6HA, U-6LPA, U-10H, U-15HA, U-108, U-108A, U-122A, U-122P, U-324A, U-340A, U-340P, U-1084A, U-2061BA, UA-340P, UA-4000, UA-4100, UA-4200, UA-4400, UA-5201P, UA-7100, UA-7200, and UA-W2A.
[0098] Examples of the urethane (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd. include AH-600, AI-600, AT-600, UA-101I, UA-101T, UA-306H, UA-306I, and UA-306T.
[0099] The ratio of the (meth)acryloyl group in the total of the epoxy group and the (meth)acryloyl group in the curable resin is preferably 30 mol% or more and 95 mol% or less. By making the ratio of the (meth)acryloyl group in this range, the adhesiveness of the obtained electronic material adhesive becomes better, and when the obtained electronic material adhesive is used as a sealant for a liquid crystal display element, the low liquid crystal contamination property becomes better.
[0100] When the obtained adhesive for electronic materials is used as a sealant for liquid crystal display elements, the curable resin preferably has a hydrogen bonding unit such as an -OH group, an -NH- group, or an -NH2 group from the viewpoint of further suppressing liquid crystal contamination.
[0101] The preferred lower limit of the content of the above-mentioned curable resin as a whole in 100 parts by mass of the adhesive for electronic materials of the present invention is 30 parts by mass, and the preferred upper limit is 90 parts by mass. By making the content of the above-mentioned curable resin as a whole within this range, the curability and adhesion of the adhesive for electronic materials obtained are more excellent. The more preferred lower limit of the content of the above-mentioned curable resin as a whole is 50 parts by mass, and the more preferred upper limit is 80 parts by mass.
[0102] The adhesive for electronic materials of the present invention preferably contains at least one selected from the group consisting of a polymerization initiator and a thermosetting agent.
[0103] Examples of the polymerization initiator include a photoradical polymerization initiator that generates radicals by light irradiation and a thermal radical polymerization initiator that generates radicals by heating.
[0104] Examples of the photoradical polymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone compounds.
[0105] Specific examples of the photoradical polymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholino)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethane-1-one, bis(2,4,6-trimethylbenzyl)-1-one, acyl) phenyl phosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propane-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyl oxime), 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and the like.
[0106] The above-mentioned radical photopolymerization initiators may be used alone or in combination of two or more.
[0107] Examples of the thermal radical polymerization initiator include thermal radical polymerization initiators composed of azo compounds, organic peroxides, etc. Among them, in order to suppress liquid crystal contamination, initiators composed of azo compounds (hereinafter also referred to as "azo initiators") are preferred.
[0108] The above-mentioned thermal radical polymerization initiators may be used alone or in combination of two or more.
[0109] Examples of commercially available products of the azo initiators include VPE-0201, VPE-0401, VPE-0601, VPS-0501, VPS-1001, V-65, and V-501 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0110] Examples of the organic peroxide include ketone peroxide, peroxyketal, hydroperoxide, dialkyl peroxide, peroxyester, diacyl peroxide, and peroxydicarbonate.
[0111] The preferred lower limit of the content of the above-mentioned polymerization initiator is 0.01 parts by mass, and the preferred upper limit is 10 parts by mass relative to 100 parts by mass of the above-mentioned curable resin. By making the content of the above-mentioned polymerization initiator within this range, the storage stability and curability of the obtained adhesive for electronic materials become more excellent. The more preferred lower limit of the content of the above-mentioned polymerization initiator is 0.1 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0112] Examples of the thermosetting agent include organic acid hydrazides, imidazole derivatives, amine compounds, polyphenol compounds, and acid anhydrides. Among them, organic acid hydrazides are preferably used.
[0113] The above-mentioned thermosetting agents may be used alone or in combination of two or more.
[0114] Examples of the organic acid hydrazide include sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide.
[0115] Examples of commercially available products of the organic acid hydrazide include organic acid hydrazide manufactured by Otsuka Chemical Co., Ltd., organic acid hydrazide manufactured by Ajinomoto Fine-Techno Co., Ltd., and organic acid hydrazide manufactured by Nippon Finechem Co., Ltd.
[0116] Examples of the organic acid hydrazide manufactured by Otsuka Chemical Co., Ltd. include SDH and ADH.
[0117] Examples of the organic acid hydrazide manufactured by Ajinomoto Fine-Techno include AJICURE VDH, AJICURE VDH-J, AJICURE UDH, and AJICURE UDH-J.
[0118] Examples of the organic acid hydrazide manufactured by Nippon Finechem Co., Ltd. include MDH and the like.
[0119] The preferred lower limit of the content of the thermosetting agent is 1 part by mass, and the preferred upper limit is 50 parts by mass relative to 100 parts by mass of the curable resin. By making the content of the thermosetting agent within this range, the thermosetting property can be made more excellent without deteriorating the coating property, storage stability, etc. of the obtained adhesive for electronic materials. The more preferred upper limit of the content of the thermosetting agent is 30 parts by mass.
[0120] The adhesive for electronic materials of the present invention may contain a silane coupling agent. The silane coupling agent mainly functions as an adhesion aid for favorably bonding the adhesive for electronic materials to a substrate or the like.
[0121] As the above-mentioned silane coupling agent, for example, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, etc. are suitably used. They are excellent in the effect of improving the adhesion to substrates, etc., and when the obtained electronic material adhesive is used as a sealant for liquid crystal display elements, the outflow of curable resin into the liquid crystal can be suppressed.
[0122] The above-mentioned silane coupling agents may be used alone or in combination of two or more.
[0123] The preferred lower limit of the content of the above-mentioned silane coupling agent in 100 parts by mass of the adhesive for electronic materials of the present invention is 0.1 parts by mass, and the preferred upper limit is 10 parts by mass. By making the content of the above-mentioned silane coupling agent within this range, the effect of improving adhesion becomes more excellent, and when the obtained adhesive for electronic materials is used as a sealant for liquid crystal display elements, the occurrence of liquid crystal contamination can be further suppressed. The more preferred lower limit of the content of the above-mentioned silane coupling agent is 0.3 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0124] The adhesive for electronic materials of the present invention may further contain additives such as a light shielding agent, a stress relaxation agent, a reactive diluent, a thixotropic agent, a spacer, a curing accelerator, a defoaming agent, a leveling agent, and a polymerization inhibitor as required.
[0125] Examples of methods for producing the adhesive for electronic materials of the present invention include a method of mixing a curable resin, an inorganic filler, a polymerization initiator, a thermosetting agent, etc. using a mixer such as a homodispersor, a homomixer, a universal mixer, a planetary mixer, a kneader, or a three-roll mill.
[0126] By blending conductive fine particles into the adhesive for electronic materials of the present invention, a vertical conductive material can be produced.
[0127] As the conductive particles, metal balls, conductive particles having a conductive metal layer formed on the surface of resin particles, etc. can be used. Among them, conductive particles having a conductive metal layer formed on the surface of resin particles are suitable because they can be electrically connected without damaging a transparent substrate, etc., due to the excellent elasticity of the resin particles.
[0128] The adhesive for electronic materials of the present invention is suitably used as a sealant for display elements, and is particularly suitably used as a sealant for liquid crystal display elements.
[0129] A liquid crystal display element including a cured product of the adhesive for electronic materials of the present invention is also one of the present invention.
[0130] The liquid crystal display element of the present invention is preferably a liquid crystal display element of narrow frame design. Specifically, the width of the frame portion around the liquid crystal display part is preferably 2 mm or less.
[0131] The coating width of the adhesive for electronic materials of the present invention when producing the liquid crystal display element of the present invention is preferably 1 mm or less.
[0132] The adhesive for electronic materials of the present invention can be suitably used for the production of a liquid crystal display element by a liquid crystal dropping method. Examples of a method for producing the liquid crystal display element of the present invention by a liquid crystal dropping method include the following method.
[0133] First, a process of applying the electronic material adhesive of the present invention on a substrate by screen printing, dispenser coating, etc. to form a frame-shaped sealing pattern is performed. Next, the following process is performed: in the uncured state of the electronic material adhesive of the present invention, tiny droplets of liquid crystal are applied to the entire surface of the frame of the sealing pattern, and another substrate is immediately overlapped. Then, a process of pre-curing the electronic material adhesive by irradiating the sealing pattern portion with light such as ultraviolet rays, and a process of heating the pre-cured electronic material adhesive to formally cure it can obtain a liquid crystal display element.
[0134] Effects of the Invention
[0135] According to the present invention, an adhesive for electronic materials having excellent drawing properties and wall residue prevention properties in a syringe can be provided. In addition, according to the present invention, a liquid crystal display element formed using the adhesive for electronic materials can be provided. DETAILED DESCRIPTION
[0136] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0137] (Preparation of surface-treated inorganic filler A)
[0138] 10 parts by mass of silica (manufactured by Nippon Shokubai Co., Ltd., "SEAHOSTAR KE-S100") was added to a Henschel mixer and dispersed in 100 parts by mass of ethanol in which 3.5 parts by mass of 3-glycidoxypropyltrimethoxysilane was dissolved. After reacting for 1 hour under reflux of ethanol, the mixture was crushed with a ball mill to prepare epoxy-treated silica (surface-treated inorganic filler A).
[0139] The particle size distribution of the obtained surface-treated inorganic filler A was measured using a particle size distribution measuring apparatus ("NICOMP 380ZLS" manufactured by Particulate Size Systems, Inc.). As a result, D50 was 970 nm and D100 was 3.2 μm.
[0140] It should be noted that the polar component δp of the Hansen solubility parameter of 3-glycidoxypropyltrimethoxysilane used as a surface treatment agent is 5.32 MPa 0.5 .
[0141] (Preparation of surface-treated inorganic filler B)
[0142] 5 parts by mass of 3-aminopropyltrimethoxysilane was used instead of 3-glycidoxypropyltrimethoxysilane. In addition, the same operation as in the above-mentioned "(Preparation of surface-treated inorganic filler A)" was performed to obtain amino-treated silica (surface-treated inorganic filler B). For the obtained surface-treated inorganic filler B, the particle size distribution was measured using a particle size distribution measuring device (manufactured by PARTICLE SIZING SYSTEMS, "NICOMP 380ZLS"), and the result was D50 of 1010nm and D100 of 3.3μm. It should be noted that the polar component δp of the Hansen solubility parameter of 3-aminopropyltrimethoxysilane used as a surface treatment agent is 4.23MPa 0.5 .
[0143] (Preparation of surface-treated inorganic filler C)
[0144] 4 parts by mass of trifluoropropyltrimethoxysilane was used instead of 3-glycidoxypropyltrimethoxysilane. In addition, the same operation as in the above-mentioned "(Preparation of surface-treated inorganic filler A)" was performed to obtain fluoroalkyl-treated silica (surface-treated inorganic filler C). For the obtained surface-treated inorganic filler C, the particle size distribution was measured using a particle size distribution measuring device (manufactured by PARTICLE SIZING SYSTEMS, "NICOMP 380ZLS"), and the result was D50 of 980nm and D100 of 3.1μm. It should be noted that the polar component δp of the Hansen solubility parameter of trifluoropropyltrimethoxysilane used as a surface treatment agent is 3.22MPa 0.5 .
[0145] (Examples 1 to 10, Comparative Examples 1 to 9)
[0146] The materials were stirred with a planetary stirring device ("Awatori Rentaro" manufactured by THINKY Corporation) according to the mixing ratios listed in Tables 1 and 2, and then uniformly mixed with a ceramic three-roll mill to obtain adhesives for electronic materials of Examples 1 to 10 and Comparative Examples 1 to 9.
[0147] In addition, ACRYSET BPF307 in the table is an acrylic rubber microparticle-dispersed bisphenol F-type epoxy compound (acrylic rubber microparticle content 19 to 21% by mass).
[0148] (Viscosity and Thixotropic Index)
[0149] The viscosity of each of the obtained adhesives for electronic materials was measured at 25° C. and 0.01 rpm using an E-type viscometer (“DV-III” manufactured by Brookfield Corporation).
[0150] For each of the obtained adhesives for electronic materials, the thixotropic index was calculated by dividing the viscosity measured at 25°C and 0.01 rpm by the viscosity measured at 25°C and 1 rpm using an E-type viscometer ("DV-III" manufactured by Brookfield).
[0151] <Evaluation>
[0152] The following evaluations were performed on each of the obtained adhesives for electronic materials. The results are shown in Tables 1 and 2.
[0153] (Prevention of wall residue in syringe)
[0154] Fill 10g of the obtained adhesive for each electronic material into a syringe (manufactured by Musashi Engineering, "PSY-10EU-OR") and install a nozzle of 0.4mmΦ. Then, use a desktop coating device (manufactured by Musashi Engineering, "SHOTMASTER 300") and an air pulse dispenser (manufactured by Musashi Engineering, "ML-808EX") to spray the adhesive for electronic materials at a pressure of 100-400kPa, and draw 9 3.5cm×3.5cm frame-shaped sealing patterns on a 15cm×15cm glass substrate. Next, after dripping 6μL of liquid crystal into the frame of each sealing pattern, repeatedly perform the operation of bonding the substrates by vacuum pressing to make a unit. At this time, the production of the unit is terminated at the moment when liquid crystal leakage occurs in all units, and the adhesive for electronic materials remaining in the syringe is measured.
[0155] The wall residue prevention property in the syringe was evaluated by evaluating the amount of adhesive for electronic materials remaining in the syringe less than 3 g as "○", 3 g or more and less than 5 g as "△", and 5 g or more as "×".
[0156] (Descriptive)
[0157] With respect to 100 parts by mass of each of the obtained adhesives for electronic materials, 1 part by mass of spacer particles (manufactured by Sekisui Chemical Co., Ltd., “Micropearl SP-2050”) having an average particle size of 5 μm was uniformly dispersed using a planetary stirring device. Next, the adhesive for electronic materials in which the spacer particles were dispersed was filled into a syringe (manufactured by Musashi Engineering, “PSY-10EU-OR”), and after degassing, the adhesive for electronic materials was applied to one of the two transparent substrates in a manner of drawing a frame-shaped sealing pattern using a dispenser (manufactured by Musashi Engineering, “SHOTMASTER300”). Then, the other transparent substrate was bonded under a reduced pressure of 5 Pa using a vacuum bonding device to obtain a unit. The obtained unit was irradiated with 100 mW / cm 2 After irradiating with ultraviolet light (wavelength 365nm) for 30 seconds, the adhesive for electronic materials was cured by heating at 120°C for 1 hour to obtain a test piece. The adhesive for electronic materials in the obtained test piece was observed, and the case where a beautiful line was drawn without a broken line or a meander in the sealing pattern was recorded as "○", the case where there was no broken line but the adhesive for electronic materials slightly meandered was recorded as "△", and the case where a broken line was recorded as "×" to evaluate the drawing property.
[0158] (Anti-insertion)
[0159] With respect to 100 parts by mass of each of the obtained adhesives for electronic materials, 1 part by mass of spacer particles (manufactured by Sekisui Chemical Co., Ltd., “Micropearl SP-2050”) having an average particle size of 5 μm is uniformly dispersed using a planetary stirring device. Next, the adhesive for electronic materials in which the spacer particles are dispersed is filled into a syringe (manufactured by Musashi Engineering, “PSY-10EU-OR”), degassed, and then the adhesive for electronic materials is applied to one of the two transparent substrates in a manner of drawing a frame-shaped sealing pattern using a dispenser (manufactured by Musashi Engineering, “SHOTMASTER300”). Next, tiny drops of liquid crystal (manufactured by Chisso, “JC-5004LA”) are applied to the entire surface of the frame of the sealing pattern, and another transparent substrate is immediately attached. Then, a metal halide lamp is used to irradiate the sealing pattern portion with 100 mW / cm 2 After irradiating with ultraviolet rays (wavelength 365 nm) for 30 seconds, the mixture was heated at 120° C. for 1 hour to obtain a liquid crystal display element.
[0160] The shape of the sealing pattern of the obtained liquid crystal element was observed. As a result, the case where the shape of the sealing pattern was not disturbed by the internal liquid crystal was marked as "○", the case where the shape of the sealing pattern was disturbed was marked as "△", and the case where the liquid crystal punctured the sealing pattern and leaked to the outside was marked as "×", and the anti-insertion property was evaluated.
[0161] (Light-shielding portion curability)
[0162] Substrate A with chromium evaporation on half of one side of Corning glass with a thickness of 0.7 mm and substrate B with chromium evaporation on the entire one side were prepared. Next, with respect to 100 parts by mass of each electronic material adhesive, 1 part by mass of spacer particles (manufactured by Sekisui Chemical Co., Ltd., "Micropearl SP-2050") with an average particle diameter of 5 μm was uniformly dispersed using a planetary stirring device. Next, the electronic material adhesive in which the spacer particles were dispersed was coated on the central part (the boundary between the chromium evaporation part and the non-evaporated part) of substrate A, substrate B was adhered, and then the electronic material adhesive was sufficiently flattened, and ultraviolet rays (wavelength 365 nm) of 100 mW / cm 2 were irradiated from the side of substrate A for 30 seconds.
[0163] Then, substrates A and B were peeled off using a cutter, and for the electronic material adhesive at a point 50 μm from the edge of the ultraviolet direct irradiation part (the part shielded by chromium evaporation), the spectrum was measured by microscopic IR method, and the conversion rate of (meth)acryloyl group in the electronic material adhesive was obtained by the following method. That is, the peak area in the range of 815 - 800 cm -1 was used as the peak area of (meth)acryloyl group, the peak area in the range of 845 - 820 cm -1 was used as the reference peak area (Japanese: リファレンスピーク面積), and the conversion rate of (meth)acryloyl group was calculated by the following formula. The case where the conversion rate of (meth)acryloyl group was 70% or more was marked as "◎", the case where it was 60% or more and less than 70% was marked as "○", the case where it was 50% or more and less than 60% was marked as "△", and the case where it was less than 50% was marked as "×", and the light-shielding portion curability was evaluated.
[0164] Conversion rate of (meth)acryloyl group = (1 - (peak area of (meth)acryloyl group after ultraviolet irradiation / peak area of reference peak after ultraviolet irradiation) / (peak area of (meth)acryloyl group before ultraviolet irradiation / peak area of reference peak before ultraviolet irradiation)) × 100
[0165] (Moisture barrier property)
[0166] The obtained adhesive for electronic materials was applied onto a smooth release film using a coater to a thickness of 200 to 300 μm. Next, a metal halide lamp was used to irradiate the film at 100 mW / cm 2 After irradiating with ultraviolet light (wavelength 365nm) for 30 seconds, the adhesive for electronic materials was cured by heating at 120°C for 1 hour to obtain a film for measuring moisture permeability. A moisture permeability test cup was prepared using the moisture permeability test method (cup method) for moisture-proof packaging materials in accordance with JIS Z0208, and the obtained moisture permeability test film was installed and placed in a constant temperature and humidity oven at 80°C and 90%RH to measure the moisture permeability. The obtained moisture permeability value was 70g / m 2 · If the time is less than 24 hours, it will be marked as "◎", and if it is more than 70g / m 2 24hr and 100g / m 2 · If the time is less than 24 hours, it will be marked as "○", and if it is more than 100g / m 2 24hr and 130g / m 2 · If the load is less than 24 hours, it will be marked as “△”. If the load is more than 130g / m 2 The case of 24 hours was marked as "×" and the moisture permeation prevention property was evaluated.
[0167] [Table 1]
[0168]
[0169] [Table 2]
[0170]
[0171] Industrial Applicability
[0172] According to the present invention, an adhesive for electronic materials having excellent drawing properties and wall residue prevention properties in a syringe can be provided. In addition, according to the present invention, a liquid crystal display element formed using the adhesive for electronic materials can be provided.
Claims
1. An adhesive for electronic materials, characterized in that: It contains curable resin and inorganic filler. The viscosity measured by an E-type viscometer at 25°C and 0.01 rpm is 1.5 million mPa·s or less, and The adhesive for electronic materials has a thixotropic index of 3.0 or more and 5.0 or less, wherein the thixotropic index is a value obtained by dividing the viscosity measured at 25° C. and 0.01 rpm using an E-type viscometer by the viscosity measured at 25° C. and 1 rpm.
2. The adhesive for electronic materials according to claim 1, wherein The content of the inorganic filler is 30 parts by mass or more based on 100 parts by mass of the curable resin.
3. The adhesive for electronic materials according to claim 1 or 2, wherein: The inorganic filler includes an inorganic filler surface-treated with a surface treatment agent, The polar component δp of the Hansen solubility parameter of the surface treatment agent is 3.5 MPa 0.5 Above and 6.0MPa 0.5 the following.
4. The adhesive for electronic materials according to claim 1 or 2, wherein: In the particle size distribution of the inorganic filler, a particle size D50 at which the cumulative mass from the smallest particle size side becomes 50% is 300 nm or more.
5. The adhesive for electronic materials according to claim 1 or 2, wherein: The inorganic filler has a particle size distribution in which a particle size D50 at which the cumulative mass from the minimum particle size is 50% is 2 μm or less, and a particle size D100 at which the cumulative mass from the minimum particle size is 100% is 6 μm or less.
6. The adhesive for electronic materials according to claim 1 or 2, wherein: In the particle size distribution, there is no organic filler having a particle size D50 of 50 nm to 500 nm at which the cumulative mass from the minimum particle size side becomes 50%, or the content of the organic filler having D50 of 50 nm to 500 nm is 10 parts by mass or less relative to 100 parts by mass of the curable resin. 7 . A liquid crystal display element comprising a cured product of the adhesive for electronic materials according to claim 1 .
Citation Information
Patent Citations
Sealing agent for dropping process of LCD panel
JP2001133794A
Curing resin composition and sealants and end-sealing materials for displays
WO2002092718A1